Edukasi Cara Membuang Masker dan Sosialisasi Manfaat Limbah Masker Dalam Menjaga Kesehatan Lingkungan di Panti Wreda Islamik Vilage Tangerang - Yoyoh, Imas; Irawati, Popy; Sekarsari, Rita (Yayasan Daarul Huda Kruengmane, 2024)
The use of disposable masks post-pandemic worldwide has increased. However, improper disposal of masks can cause environmental contamination and increase the risk of spreading disease, especially in age groups that are susceptible to disease, such as the elderly in nursing homes, so it is necessary to provide education and socialization through community service activities. The purpose of this community service activity is to provide education on how to properly dispose of masks and socialization regarding the use of mask waste in maintaining environmental health at the Panti Wreda Islamik Village Tangerang. The methods used in this activity include counseling, direct demonstrations, and interactive discussions with residents and managers of the shelter. The results of the activity showed an increase in awareness and understanding of residents and managers of the shelter regarding the importance of managing mask waste. This activity is expected to have routine monitoring and further implementation in maintaining environmental cleanliness and improving the quality of life at the Panti Wreda Islamik Village Tangerang.